Pharmacokinetics of Caffeic Acid, Ferulic Acid, Formononetin, Cryptotanshinone, and Tanshinone IIA after Oral Administration of Naoxintong Capsule in Rat by HPLC-MS/MS. (5th July 2017) - Li, Jin; Bai, Yang; Bai, Yun; Zhu, Ruichao; Liu, Wei; Cao, Jun; An, Mingrui; Tan, Zhijing; Chang, Yan-xu
Abstract : Naoxintong capsule (NXTC) was a famous patent medicine of Traditional Chinese Medicine (TCM) to treat cerebrovascular diseases in China. An LC-MS/MS method was developed for simultaneous determination of 11 major ingredients (paeoniflorin, ecdysterone, amygdalin, mulberroside A, caffeic acid, ferulic acid, salvianolic acid B, astragaloside IV, formononetin, cryptotanshinone, and tanshinone IIA) in NXTC in rat plasma. All analytes were separated on an Eclipse plus C18 column using a gradient mobile phase system of acetonitrile-0.1% formic acid aqueous solution. The lower limits of quantification of 11 ingredients were between 0.075 and 10 ng mL −1 . The precision was less than 15% and the accuracies were between 85% and 115%. The results showed that caffeic acid, ferulic acid, formononetin, cryptotanshinone, and tanshinone IIA could be detected after oral administration of NXTC. The validated method was successfully applied to pharmacokinetic study of the caffeic acid, ferulic acid, formononetin, cryptotanshinone, and tanshinone IIA in rats after oral administration of NXTC at single and triple dose.